Elastic Optical Networks: The Global Evolution to Software Configurable Optical Networks. (December 2013) - Layec, Patricia; Morea, Annalisa; Vacondio, Francesco; Rival, Olivier; Antona, Jean‐Christophe; Leven, Andreas; Varma, Eve L.
Abstract Worldwide operator deployment of high‐speed 100G coherent optical networks is currently underway. To ensure a competitive solution offering significant performance improvements to cope with the ever‐increasing traffic demand, a novel network concept has been proposed for improved resource utilization based on "elasticity"; specifically, the ability to make a number of previously fixed transmission parameters tunable, for example optical data rate or channel spacing. The benefits are numerous, including increased network capacity, lower cost per bit, and improved energy efficiency and scalability. In this paper, we review the work carried out within the Cooperation for a Sustained European Leadership in Telecommunications (CELTIC) Elastic‐Optical NETwork (EO‐Net) project towards advancing the state of software‐configurable optical networking. We identify the key building blocks for enabling elastic optical networks to provide desired performance improvements over static optical networks. We examine the design of elastic transponders capable of data rate adaptation, interfaces between client packet devices and transponders supporting flexible traffic aggregation, and associated algorithms for traffic grooming and routing. We also perform network cost/energy analyses. Finally, we review the experimental demonstration of such elastic functionalities. © 2013 Alcatel‐Lucent.